The Effect of Gingival Retraction Procedures on Periodontal Indices and Crevicular Fluid Cytokine Levels: A Pilot Study - Jian Feng, DMD;1 Hoda Aboyoussef, DMD, MS;2 Saul Weiner, DDS;3 (Journal of Prosthodontics, 2006)
The purpose of this study was to examine the effects of placement of retraction cord subgingivally upon periodontal indices including plaque index (PI), gingival index (GI), pocket depth (PD), bleeding on probing (BOP), and attachment level (AL), as well as gingival crevicular fluid (GCF) and TNF-Î± levels.